2005
DOI: 10.7748/ns.19.38.51.s50
|View full text |Cite
|
Sign up to set email alerts
|

Reporting incidents of violence and aggression towards nhs staff

Abstract: Violence and aggression against nursing staff have been the subject of an ongoing campaign. However, incidents of violence continue to be under-reported. This article discusses factors leading to under-reporting of incidents and focuses on how nursing staffs' attitudes and responses to violence may contribute to the likelihood of reporting incidents. Change management techniques are proposed to address the under-reporting of incidents and to improve the work environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 0 publications
1
56
0
Order By: Relevance
“…For example, an incident may be recorded as physical abuse when, in fact, no physical contact occurred. Fourth, due to factors such as variability in the views of staff about what constitutes a reportable incident [4,44,45] and the perception held by many nurses that violent patients are under significant stress and are therefore not fully responsible for their behaviour [46], it is likely that the 208 incidents recorded in IIMS during the three-year study period are an underestimate of the true incidence of workplace violence among the study population. This is supported by our recent work surveying levels of violence among Justice Health staff, which found that 264 survey respondents had experienced at least one violent incident in their workplace during a three-month recall period, and that patients/prisoners were the primary source of aggression [23] (the quarterly average number of violent incidents recorded in IIMS during the study period was 17.4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an incident may be recorded as physical abuse when, in fact, no physical contact occurred. Fourth, due to factors such as variability in the views of staff about what constitutes a reportable incident [4,44,45] and the perception held by many nurses that violent patients are under significant stress and are therefore not fully responsible for their behaviour [46], it is likely that the 208 incidents recorded in IIMS during the three-year study period are an underestimate of the true incidence of workplace violence among the study population. This is supported by our recent work surveying levels of violence among Justice Health staff, which found that 264 survey respondents had experienced at least one violent incident in their workplace during a three-month recall period, and that patients/prisoners were the primary source of aggression [23] (the quarterly average number of violent incidents recorded in IIMS during the study period was 17.4).…”
Section: Discussionmentioning
confidence: 99%
“…Almost certainly an underestimate, this figure represents the tip of the iceberg when considered in relation to non-fatal violent incidents [1]. Although we tend to think of violence as something that occurs in the home or community, violence in the workplace is common [2,3] and incidents often go unreported [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…In part, this may be because these behaviors are learned in the schoolyard where most bullying among girls is relational, covert and socially toxic-ostracism, insults, divisive gossip, and so on-the same behaviors that are demonstrated in the workplace (Farrington, 1993;Rayner & Hoel, 1998;Vessey, DeMarco, Gaffney, & Budin, 2009). BHHV, surrounded by a "culture of silence," fears of retaliation, and the perception that "nothing will be changed," can also effectively shut down the exchange of information (DeMarco, 1998;Ferns, 2005;Stearley, 1997). Data support these assertions.…”
Section: Prevalence Of Bhhvmentioning
confidence: 97%
“…As with other forms of victimization, signifi cant underreporting is likely (Ferns & Chojnacka, 2005;NACNEP, 2007). Frequent low-grade BHHV goes unnoticed by others and the recipient may not report such incidents for fear of appearing petty.…”
Section: Prevalence Of Bhhvmentioning
confidence: 98%
“…Successful workplace violence prevention programs encourage reporting of all incidents, so they can be investigated to assist with prevention of similar incidents in the future [33]. The literature suggests that employees are more likely to report incidents when the process is simple and not time consuming [4,9]. …”
Section: Course Contentmentioning
confidence: 99%